KEDUDUKAN UNDANG-UNDANG NOMOR. 11 TAHUN 2020 SETELAH PUTUSAN MAHKAMAH KONSTITUSI NOMOR 91/PUU-XVIII/2020 - Imon, Linda Lidia (At-Tanwir Law Review, 2025)
According to Ahmad Rendi, the approach to making rules and regulations to simplify them, known as "omnibus law", must meet several factors, namely: (1) Multisector or consisting of many sector burdens with the same theme; (2) many articles, as a result many sectors are discussed; (3) many laws and regulations are collected into one new law; (4) independent or independent, not bound by or minimally related to other regulations; and (5) eliminate/revoke some and/or all other regulations. Omnibus law is a strategy or approach to create legislative norms through one law that simultaneously changes many articles in various other laws to achieve state policy, which is very significant.